FASHION THRIFT SEBAGAI MEDIA KOMUNIKASI ARTIFAKTUAL DALAM PEMBENTUKAN IDENTITAS SOSIAL MAHASISWI FISIP UNIVERSITAS RIAU - Pamela, Kessy; ', Yasir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Fashion and clothing are used as the delivery of non-verbal messages about one's self to others. It also makes how Thrift fashion enthusiasts communicate themselves when wearing Thrift fashion. Various kinds of assumptions about Thrift attract the attention of researchers to dig deeper into the meaning of fashion as communication in fashion Thrift. This research is a descriptive qualitative research using data collection techniques through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman models. The results of this study indicate that because of motives that influence FISIP University of Riau students to use Fashion Thrift in their daily style are social environment factors, social media or mass media and places close to secondhand shops. Meanwhile, in order to motive, FISIP University of Riau students use thrift, namely to appear fashionable, reduce used clothing waste and as a sustainable fashion movement or sustainable fashion Keywords: Artifactal Communication, Thrift, Because Of Motive, In Order To Motive